The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1055/s-0034-1390866
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pancreatitis caused by a swallowed orthodontic device

Abstract: Cases and Techniques Library (CTL) E667Tiller Maximilian et al. Chronic pancreatitis from a swallowed orthodontic device … Endoscopy 2014; 46: E667-E668This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
8
0
2
Order By: Relevance
“…At the chronic stage, some foreign bodies might form biliary stones, which may cause the cholangitis [11] or cholecystitis [12]. Moreover, the foreign body may also cause chronic pancreatitis [13].…”
Section: Discussionmentioning
confidence: 99%
“…At the chronic stage, some foreign bodies might form biliary stones, which may cause the cholangitis [11] or cholecystitis [12]. Moreover, the foreign body may also cause chronic pancreatitis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed symptoms presents as with acute mediastinitis with chest pain with signs of pleural effusion and acute/subacute peritonitis. Uday Kumar Umesan et al 2012 reported a case of accidental aspiration of arch wire segment during adjustment and were located at the laryngeal region that necessitated endoscopic retrieval in the hospital [24,[25][26][27][28][29].…”
Section: "Fbs" Impacted At Gastrointestinal Perforationmentioning
confidence: 99%
“…The principal responsibility of an orthodontist is to assess the amount of cooperation that can be achieved from the patients and their parents during treatment. So an orthodontist must check complete cooperation and persistent controlling of their children to confirm that professional instructions are respected [10,16,23,24,26,27].…”
Section: Case Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of reported cases in orthodontics is considerably less common but no less varied in the range of objects involved, and these include brackets, bands, second molar buccal tubes, transpalatal arches, removable appliances and appliance fragments, archwire fragments, sectional archwires, coil springs, expansion appliance keys, retainers, and quadhelices [ 2 , 3 , 4 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. A literature review was carried out using the PubMed database to search for case reports relating to ingestion or aspiration of foreign bodies of orthodontic origin.…”
Section: Introductionmentioning
confidence: 99%